2020
DOI: 10.1007/s10953-020-00981-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Mechanism of Palladium(II) Extraction from Chloride Media with N-Hexadecylpiperidinium Chloride

Abstract: N-hexadecylpiperidinium chloride ([PIP16]Cl) has been synthesized and examined as a reagent for extractive recovery of palladium(II) from hydrochloric acid solutions. The effect of the contact time between the two phases, temperature and the concentration of palladium(II) ions, the extractant and HCl, were also evaluated. The anion-exchange mechanism of palladium(II) extraction with [PIP16]Cl was confirmed by Job's method, UV-VIS, IR and 1 H NMR analysis. The extraction of palladium(II) from 0.1 mol•L −1 HCl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The results suggest that the extraction of Pd(II) with TBAB proceeds according to the anion-exchange mechanism, similar to the extraction with Cyphos IL 104 [31,32], where the anionic group of the ionic liquid is re-placed by the chlorocomplex anion [28]. Cieszynska and Wieczorek [29] reported that palladium(II) is extracted from 0.1 mol•dm −3 HCl to the organic phase of the molar ratio of 1:2. Thus, it can be concluded that palladium(II) is extracted to the organic phase according to the following equation:…”
Section: Solvent Extraction Of Pd(ii) By Tbabmentioning
confidence: 72%
See 1 more Smart Citation
“…The results suggest that the extraction of Pd(II) with TBAB proceeds according to the anion-exchange mechanism, similar to the extraction with Cyphos IL 104 [31,32], where the anionic group of the ionic liquid is re-placed by the chlorocomplex anion [28]. Cieszynska and Wieczorek [29] reported that palladium(II) is extracted from 0.1 mol•dm −3 HCl to the organic phase of the molar ratio of 1:2. Thus, it can be concluded that palladium(II) is extracted to the organic phase according to the following equation:…”
Section: Solvent Extraction Of Pd(ii) By Tbabmentioning
confidence: 72%
“…As can be seen, ionic liquids (ILs) are very often used as the carriers of metal ions for membrane synthesis [8][9][10][11][12][13][21][22][23][24] and as the extractants of PGMs [10,[26][27][28][29][30][31][32] in the conventional solvent extraction process. However, there have been no reports to date on palladium(II) transport using PIMs with TBAB.…”
Section: Introductionmentioning
confidence: 99%
“…41 In contrast to “simple” amines used as extractants for Pd( ii ) whose effectiveness is weakly dependent on the acidity of the aqueous medium within a low pH range, 35,44 diamines capable of forming chelates with Pd( ii ) extract palladium most effectively at pH 1–2. 45,46…”
Section: Resultsmentioning
confidence: 99%
“…41 In contrast to ''simple'' amines used as extractants for Pd(II) whose effectiveness is weakly dependent on the acidity of the aqueous medium within a low pH range, 35,44 diamines capable of forming chelates with Pd(II) extract palladium most effectively at pH 1-2. 45,46 Therefore, the maximum efficiency of compound 6 at pH E 1 is natural. A decrease in the extraction efficiency of compound 6 at a pH o 1 may have a kinetic nature.…”
Section: Selectivity Of the Extraction Of Pd(ii) From Mixtures Contai...mentioning
confidence: 99%
“…The palladium-containing solutions used for extraction were prepared according to the procedure described in [13][14][15][16][17]. Separate solutions of bis-(2-hydroxyl-5-alkylbenzyl)amine in kerosene were used as extractants, followed by stirring an organic solution with an equal volume of 1 M NaOH, and then with water.…”
Section: Methodsmentioning
confidence: 99%